Kedudukan Perempuan dalam Al-Qur’an Studi Komparasi Penafsiran Fakhruddin Ar-Razi dan Mutawalli Asy-Sya’rawi atas QS. Ar-Rum 21: The Position of Women in the Qur'an: A Comparative Study of the Interpretation of Fakhruddin Ar-Razi and Mutawalli Asy-Sya'rawi on the QS. Ar-Rum 21 - Almas Ma'ruf Baihaqi; Muhammad Hasyim Ramadhani; Nila Asqinatus Sulfa (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2025)
This research is motivated by the importance of understanding the position of women in Islam, particularly in the context of Qur’anic exegesis of Surah Ar-Rum: 21, which emphasizes the role of women in building both family. The differences in interpretation among various exegetes necessitate a comparative study of two prominent scholars, Fakhruddin Ar-Razi and Mutawalli Asy-Sya’rawi. In this verse, the role of women is highlighted primarily as wives who provide tranquility, affection, and harmony within the family, while at the same time reflecting values of mercy and compassion that extend to a broader contribution in building society. The method employed is library research with a qualitative approach, analyzing comparatively Ar-Razi’s Mafatih al-Ghayb and Asy-Sya’rawi’s Tafsir Khawatir along with other supporting literature. The findings reveal that both exegetes agree that women are a divine blessing and a complement to men, with mutually supportive roles in the family. However, Ar-Razi emphasizes differences in obligations based on nature from a philosophical and conservative standpoint, while Asy-Sya’rawi adopts a moderate and contextual approach that relates role distinctions to human disposition (fitrah) and divine law (sunnatullah) as well as modern social relevance. Asy-Sya’rawi’s interpretation is more adaptive to contemporary change, while Ar-Razi provides a classical intellectual foundation that remains significant for exegetical studies.